Emerging Technologies for Timely Point‐of‐Care Diagnostics of Skin Cancer - Jarrod L. Thomas; Adrian H. M. Heagerty; Pola Goldberg Oppenheimer (Global Challenges)
Abstract Skin cancer is a global health crisis and a leading cause of morbidity and mortality worldwide. A leading factor of malignancy remains the UV radiation, driving various biomolecular changes. With shifting population behaviors, deficiency in screening programs and reliance on self‐presentation, climate change and the ageing world populace, global incidents have been surging alarmingly. There is an urgent need for new technologies to achieve timely intervention through rapid and accurate diagnostics of skin cancer. Raman spectroscopy has been emerging as a highly promising analytical technology for diagnostic applications, poised to outpace the current costly, invasive and slow procedures, frequently hindered by varying sensitivity, specificity and lack of portability. Herein, complex and intricate progress are overviewed and consolidated across medical and engineering disciplines with a focus on the latest advances in the traditional and emerging skin cancer diagnostics. Methods detecting structural and chemical responses are categorized along with emerging chemo‐biophysical sensing techniques. Particular attention is drawn to Raman spectroscopy, as a non‐invasive, rapid and accurate sensing of molecular fingerprints in dermatological matrix with an additional focus on artificial intelligence, as a decision support tool collectively, laying the platform toward development and rapid translation of point‐of‐care diagnostic technologies for skin cancer to real‐world applications.